An effective training system for endoscopic submucosal dissection of gastric neoplasm - Tsuji, Y.; Ohata, K.; Sekiguchi, M.; Ito, T.; Chiba, H.; Gunji, T.; Yamamichi, N.; Fujishiro, M.; Matsuhashi, N.; Koike, K. (Endoscopy, 2011)
Background and study aims: A standard training system for endoscopic submucosal dissection (ESD) remains to be established. In this study, we evaluated the validity of our training program for gastric ESD. Patients and methods: Four trainees performed gastric ESD for a total of 117 lesions in 107 patients (27 to 30 consecutive lesions per trainee) at a tertiary referral center during 2 years in the training program. Trainees, who already had the fundamental skills and knowledge needed for ESD, each assisted at 40 gastric ESD procedures, then in 20 cases applied post-ESD coagulation (PEC) to gastric mucosal defects; they then began to perform ESD, starting with gastric antral lesions. Treatment outcomes, including mean procedure time, and rates of en bloc resection, en bloc plus R0 resections, complications, and self-completion, were evaluated, for the initial 15 and subsequent 12 to 15 cases. Results: Overall rates of en bloc resection and en bloc plus R0 resection were as high as 100 % and 96.6 %, respectively. Regarding complications, seven cases of delayed hemorrhage (6.0 %) and three cases of perforation (2.6 %) occurred; all complications were solved endoscopically. The most frequent reason for operator change was lack of submucosal dissection skill. The self-completion rate was more than 80 % even in the early period, and did not increase for later cases. Conclusions: Our training system enabled novice operators to perform gastric ESD without a decline in clinical outcomes. Key features of this training are prior intensive learning and actual ESD during the learning period under expert supervision.